Comparison of diagnostic performances of ten different immunoassays detecting anti-CCHFV IgM and IgG antibodies from acute to subsided phases of Crimean-Congo hemorrhagic fever. - Petra Emmerich; Ronald von Possel; Christina Deschermeier; Salih Ahmeti; Lindita Berisha; Bahrije Halili; Xhevat Jakupi; Kurtesh Sherifi; Claudia Messing; Viola Borchardt-Lohölter (Public Library of Science (PLoS), 2021)
Crimean-Congo Hemorrhagic Fever Virus (CCHFV) is a geographically widespread tick-borne arbovirus that has been recognized by the WHO as an emerging pathogen needing urgent attention to ensure preparedness for potential outbreaks. Therefore, availability of accurate diagnostic tools for identification of acute cases is necessary. A panel comprising 121 sequential serum samples collected during acute, convalescent and subsided phase of PCR-proven CCHFV infection from 16 Kosovar patients was used to assess sensitivity. Serum samples from 60 healthy Kosovar blood donors were used to assess specificity. All samples were tested with two IgM/IgG immunofluorescence assays (IFA) from BNITM, the CCHFV Mosaic 2 IgG and IgM indirect immunofluorescence tests (IIFT) from EUROIMMUN, two BlackBox ELISAs for the detection of CCHFV-specific IgM and IgG antibodies (BNITM), two Anti-CCHFV ELISAs IgM and IgG from EUROIMMUN using recombinant structural proteins of CCHFV antigens, and two ELISAs from Vector-Best (IgM: μ-capture ELISA, IgG: indirect ELISA using immobilized CCHFV antigen). Diagnostic performances were compared between methods using sensitivity, specificity, concordance and degree of agreement with particular focus on the phase of the infection. In early and convalescent phases of infection, the sensitivities for detecting specific IgG antibodies differed for the ELISA test. The BlackBox IgG ELISA yielded the highest, followed by the EUROIMMUN IgG ELISA and finally the VectorBest IgG ELISA with the lowest sensitivities. In the subsided phase, the VectorBest IgM ELISA detected a high rate of samples that were positive for anti-CCHFV IgM antibodies. Both test systems based on immunofluorescence showed an identical sensitivity for detection of anti-CCHFV IgM antibodies in acute and convalescent phases of infection. Available serological test systems detect anti-CCHFV IgM and IgG antibodies accurately, but their diagnostic performances vary with respect to the phase of the infection.